Classification of regional language diversity in the maluku region using decision trees - Ghyovanno Godlif Tomhisa; Wilma Latuny; Yoakhina Nicole Makaruku; Jermias Victor Manuhutu; Hendri Hawurubun (Jurnal Mantik, 2026)
Regional languages are an important part of cultural heritage that reflect the identity, values, and character of a community. In Maluku Province, there is a high degree of linguistic diversity because the region consists of many islands with different community characteristics. However, the passage of time, modernization, and population mobility have led to a decline in the number of speakers in some areas, threatening the extinction of a number of regional languages. This study aims to classify and visualize the diversity of regional languages in Maluku Province using the Decision Tree algorithm. This method was chosen because it is capable of recognizing patterns and relationships between variables, such as region, number of speakers, and language vitality. The research data was obtained from the compilation of the Language Agency and field observations, then processed using Python with the help of the pandas, scikit-learn, matplotlib, and Streamlit libraries to produce an interactive analytical dashboard. The results showed that regional languages on Seram Island, such as Tana, Alune, and Wemale, had higher vitality levels than languages in other regions. The Decision Tree model built was able to classify language status with an accuracy rate of 92%. The resulting visualization provided a clear picture of the actual condition of regional languages in Maluku and could be used as a basis for regional language preservation and development efforts by local governments.